Implantation of computed tomography-guided Iodine-125 seeds in combination with chemotherapy for the treatment of stage III non-small cell lung cancer - Huo, Xiaodong; Huo, Bin; Wang, Huixing; Wang, Lei; Cao, Qiang; Zheng, Guangjun; Wang, Junjie; Chai, Shude; Zhang, Zuncheng; Yang, Kuo; Niu, Yuanjie; Wang, Haitao (Journal of Contemporary Brachytherapy, 2017)
Purpose : We investigated the role of computed tomography (CT)-guided Iodine-125 ( 125 I) seed implantation in combination with chemotherapy for the treatment of stage III non-small cell lung carcinoma (NSCLC). Material and methods : The data from 182 patients with stage III NSCLC who were treated with radioactive 125 I seed implantation between June 2002 and June 2009, and who received sequential platinum-based combination chemotherapy using the most common combination of platinum and gemcitabine, were retrospectively reviewed. The 182 patients received a prescribed dose of 110.0 Gy, with a median radioactivity of 0.70 mCi (range, 0.64-0.78 mCi, 2.37-3.26 × 107 Bq). The median number of 125 I seeds was 38 pellets (range, 6-105 pellets). The median post-operation dose covering 100% of the target volume (D 100 ) was 94.5 Gy (range, 54.6-125.5 Gy). The median D 90 was 143.0 Gy (range, 121.6-184.0). Results : The 1-, 3-, and 5-year overall survival rates were 83.35%, 25.57%, and 11.34%, respectively; the median survival time was 24.76 months. At 1, 3, and 5 years, the local control rates were 92.01%, 86.51%, and 76.45%, respectively; the median local control time was 25.28 months. For patients with stage IIIA and IIIB NSCLC, the median survival times were 26.67 and 24.59 months, respectively (p = 0.2). Pre-treatment hemoglobin level, tumor volume, and postoperative D 100 were significantly associated with survival. A total of 24 patients experienced pneumothorax (incidence rate, 13.20%), and 17 patients experienced hemothorax (incidence rate, 5.0%). Conclusions : CT-guided 125 I seed implantation combined with chemotherapy is an effective, minimally invasive method for the treatment of stage III NSCLC. Furthermore, hemoglobin levels before treatment, D 100 , and the maximum diameter of the tumor may be prognostic factors in patients with NSCLC treated sequentially with radiotherapy and chemotherapy.